Household food security during the COVID-19 pandemic in urban and semi-urban areas in Indonesia - Ahmad Syafiq; Sandra Fikawati; Syilga Cahya Gemily (BMC, 2022)
Abstract Background One of the impacts of the COVID-19 pandemic was the weakening of the community's economic condition. The weak economy of the community will have an impact on household food security. This study aims to determine food security in the COVID-19 pandemic situation and the impact of the pandemic on food security in urban and semi-urban areas. Methods A cross-sectional study with a total sample of 517 people who live in urban (Jakarta) and semi-urban (Depok) areas. The research data was collected online and purposively through Posyandu cadres who have access to family/community. Food security was measured using HFIAS (Household Food Insecurity Access Scale) method, while impact of COVID-19 pandemic was categorized into two categories: impacted (reduced income and laid off) and less impacted (not reduced income and laid off). Data analysis used the Chi-square test and multiple logistic regression. Results There were 65.0% of households with various level of food insecurity during the COVID-19 pandemic. The results of the multivariate analysis showed that family income during the COVID-19 pandemic (AOR = 4.2; CI = 2.7-6.7), the type of impact of the COVID-19 pandemic, i.e., reduced income and stopped working (AOR = 2.6; CI = 1.6-4.1), and the age of the respondent (AOR = 1.7; CI = 1.1-2.5) were significantly related to household food security during the pandemic after being controlled by husband's work status. Households with lower income had 4 times higher risk to experience food insecurity compared to those with higher income. Heavily impacted households (through reduced income and stopped working) had 3 times higher risk to experience food insecurity compared to those who did not. Additionally, we found that households with younger respondent (< 31 years old) had 2 times higher risk to experience food insecurity compared to those older counterparts. Conclusions The COVID-19 pandemic impacted household food security in both urban and semi-urban areas through worsening employment status and income condition.